(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
Nitrogen and dry matter disappearance of sesame seed cake treated with ethanol (50% and 70%) at 78⁰C and 10% tallow were estimated. Rumen degradability was carried in three fistulated bulls fed sorghum stover as basal diet with 2 kgs supplemental concentrate and salt lick stone, three bags (a bag in bull at a time) from each treatment were incubated for 0, 3, 6, 12, 24, 36, and 48 hours. In situ crude protein and dry matter, potential degradability, soluble fraction and effective rumen degradability for treated sesame cake were significantly (P <0.05) lower compared with untreated sesame seed cake. The maximum reduction in CP degradability was reported in 50% ethanol, 70%ethanol and 10% tallow respectively. Ethanol treatment protected protein from being degraded by microflora, and would be expected to improve nitrogen utilization